Há saídas? As saídas. Pelos caminhos dos cotidianos das vidas de adolescentes após cumprimento de medida socioeducativa em meio fechado - Faria, Caroline Beier (2017)
Poor childhood and adolescence has undergone a social stigmatization process taking a cultural imaginary status as “dangerous” and “violent”. Brazilian Government has developed controlling and contention tools as a response to the involvement of adolescents in infractions. The Statute of the Child and Adolescent (Estatuto da Criança e do Adolescente – ECA) has made it possible to give these tools a punitive formal profile, in the juridical text, working on socioeducation, and blaming the adolescents, families, and society. Within this context, the present study aimed to know the expectations from juveniles regarding the process of quitting the internment, as well as learning how its routine goes on. The study was at two foundations where the appropriate socioeducational matters of privation of liberty were performed, in two different states of Brazil, being one in a medium-size city, and the other in a metropolis. Thus, during the first stage, 22 workshops meetings were carried out with 59 adolescents, aiming to know their expectations regarding quitting the foundation, and they were also invited to take part into the second stage. Nine semi-structured interviews were also done with technicians involved in their follow-up, focusing on strategies used to plan their reintroduction to the community. In the second stage, territorial follow-ups were performed, for four months, with four adolescents who were interned in socioeducational privacy of liberty in one of the cities mentioned before, aiming to understand how their return to the community was. By using the data obtained from the foundations, and together with the teenagers in their communities, we were able to understand that those adolescents were subordinate to criminal subjection social process, by creating the social expectation which bonds them to the identity of criminals, highly highlighting them to the possibility of communal bonding. It was concluded that besides the strong tagging of this process, and the exclusion from the daily life they face, since their internment the adolescents aim to build resistance and life spaces in their routines.